Morphometric, phylogenetic analyses and dna barcoding of pangasiid catfishes (Teleostei: Pangasiidae) in Peninsular Malaysia / Haslawati Baharuddin - Haslawati , Baharuddin (2016)
Fishes of the family Pangasiidae are medium to large sized catfishes with diverse morphologies and ecologies, ranging from 20-300 cm in length, with most species being more than 50cm long. Pangasiids are generally found in freshwater, however, some species also live in brackish and marine waters. Taxonomic ambiguities arise due to morphological variations between conspecifics found on the Asian Mainland and the Indo-Malayan Archipelago, morphologically disparate life stages and species complexes as well as local scale ecological variations. This work examined the diversity and distribution of pangasiids in Peninsular Malaysia based on past and present collections (n=161 specimens) using 35 morphometric measurements and five meristic counts. Identification keys established were based on seven morphological species from four genera; Pangasianodon, Pangasius, Pseudolais and Helicophagus. Four native species were confirmed, together with an introduced aquaculture species from Thailand, Pangasianodon hypophthalmus. Three other species: two species previously known only from Indo-China (Pangasius bocourti and Pangasius conchophilus) and one from Indonesia (Pangasius djambal) were also identified. A minimum of three characters: (1) palatal dentition, (2) head shape and (3) gill raker counts, were found to be useful distinguishing features. Previously unnoticed, Pangasius polyuranodon can now be positively distinguished from the more abundant Pseudolais micronemus by several characters: a distinctive palatal dentition, longer maxillary and mandibular barbels, higher count of anal-fin rays, higher counts of gill rakers on the first gill arch, longer caudal peduncle, wider anterior snout and wider mouth. Clarification on the identity between this two morphologically similar species is important in drafting proper conservation measures, since they have different ecological and biological requirements. Many native pangasiid species are threatened in the wild due to hybridisation and introduction of nonnative species, through fishing pressure, habitat degradation and aquaculture practices. This study demonstrates the strong potential of cytochrome C oxidase subunit I (COI) DNA barcoding as an identification tool in detecting potentially threatened as well as invasive pangasiids. A neighbour-joining (NJ) dendogram generated five groups representing four distinct genera. The genus Pangasius was further subdivided into two clades, with a mixture of morphospecies: (i) P. bocourti-P. djambal and (ii) P. nasutus- P. conchophilus. A barcode gap was detected using corrected Kimura-2-Parameter (K2P) genetic distance with higher intraspecific value (5.1%) compared to interspecific distance (3.0%), suggesting the possibility of a species complex, hybridisation or incorrect taxonomic identification, following unclear species delineation for P. conchophilus. Despite this complexity, Automatic Barcode Gap Discovery (ABGD) analysis revealed potential barcode gaps for most species pairs. This study also showed that both mitochondrial regions (16S rRNA and COI) can be used for taxonomic purpose. Nevertheless, COI showed better performance in species delineation. The phylogenetic and sequence analyses revealed that closely related species, despite their origin, are important in conservation measures. K2P genetic distance revealed seven molecular groupings, which were congruent with the morphological species. This study clarified and established the diversity of Pangasiidae in Peninsular Malaysia, thus connecting the gap between the two previous pangasiid distributions.